DIGITALISASI TATA KELOLA PEMBIAYAAN PENDIDIKAN: PELUANG DAN TANTANGAN IMPLEMENTASI E-RKAS - Trimiltin, Ricky; Ahmad, Masduki (STKIP Pesisir Selatan, 2025)
This study aims to analyse the opportunities and challenges of implementing e-RKAS (electronic-based School Activity and Budget Plan) as part of efforts to digitize education financing governance in Indonesia. The main focus of this study is how e-RKAS contributes to improving transparency, efficiency and accountability in the management of BOS Funds at the education unit level. Methods: The method used is a systematic literature review (SLR) with a qualitative approach. Data sources were collected from relevant national and international literature, published between 2015 and 2025, using keywords such as “e-RKAS”, “education financing” and “BOS governance”. Analysis was conducted using thematic coding techniques to identify key issues that emerged from previous studies. Results: The results show that e-RKAS provides a strategic opportunity to accelerate the disbursement process, strengthen the integration of digital financial reporting, and encourage the implementation of school-based management. However, significant challenges such as limited technological infrastructure, low digital literacy of school managers, and lack of training and technical assistance are still obstacles in the implementation of this system. Novelty: The novelty of this research lies in the systematic mapping of the actual conditions of e-RKAS implementation nationwide, as well as the formulation of evidence-based strategic recommendations to strengthen the success of digitizing education financing in the future.